A matlab-based graphical user interface (GUI) to predict the food quality during frying process - Siti Nabihah, Othman (2022)
The phenomena of heat and mass transfer are occur during deep frying process due to physicochemical changes that affects the colour and moisture content of food quality. The inconsistent quality of fried foods makes it gruelling to fabricate luscious and satisfying fried foods at all times. Therefore, there is a need to predict the dynamics colour and moisture content of food such as fries, nugget, chicken pie and so on. In this study, the colour and moisture content of French fries is studied during deep frying.The colour changes and moisture content were formulated by first order kinetic equation which was numerically solved by using the Runge Kutta fourth order method that was embedded with a parameter fitting technique called as Nelder-Mead algorithm in MATLAB software. The Arrhenius equation is used in this model. Then, the sum squared error (SSE) of modified model was compared with the SSE of existing model. The colour and moisture content were evaluated based on two parameters of French fries, which were oil temperature (150℃,170℃ and 190℃) and sample thickness (5mm,10mm and 15mm) during deep frying. The results showed that the modified model has lower SSE value as compared to the existing model. The user-friendly graphical user interface (GUI) could give a better understanding about frying and was beneficial to food industry players who have limited experience in mathematical model and programming skills.